Overview of Poultry Eimeria Life Cycle and Host-Parasite Interactions - López-Osorio, Sara; Chaparro-Gutiérrez, Jenny J.; Gómez-Osorio, Luis M. (Frontiers in Veterinary Science, 2020)
Apicomplexan parasites of the genus Eimeria are organisms which invade and multiply in the intestinal tract, causing coccidiosis, an enteric disease of major economic importance worldwide. The disease cause production losses and high morbidity ranging from an acute, bloody enteritis, with high mortality, to being subclinically silent. However, intestinal lesions of the infection vary, depending on the species of coccidian. The most important Eimeria species are: E. tenella, E. necatrix, E. acervulina, E. maxima, E. brunetti, E. mitis, and E. praecox. The level of dietary protein plays a key role on the response against coccidiosis in vaccinated and unvaccinated birds, the former basically consist of a challenge with attenuated strains of Eimeria. The present paper reviews the taxonomy, life cycle, cellular development, pathogenicity, and the effect of feed protein and amino acids levels in poultry coccidiosis.